A device to collect passive, flow‐weighted water samples from surface runoff. Issue 6 (3rd September 2022) - Maris, Jacob O.; Stewart, Ryan D.
Abstract: Obtaining water quality samples from surface runoff is essential for understanding erosion and pollutant transport processes. Existing water sampling devices are expensive, require installation of extensive infrastructure or power supplies, or have limited ability to collect flow‐weighted samples. We created an inexpensive, nonpowered, flow‐weighted water sampling device that can be incorporated into runoff quantification systems like the Upwelling Bernoulli Tube (UBeTube). Our device, called the Holey Sampler, consists of a standpipe with holes drilled at specific heights. Water enters the standpipe in proportion to the water flow rate through the UBeTube and is routed to an external collection bottle. We built and tested two versions of the Holey Sampler that sampled water at an approximate ratio of 1:250 of the runoff rate. The Standard Opening Holey Sampler (Standard‐OHS) configuration was made with 1.6‐mm‐diam. holes, whereas the Miniature Opening Holey Sampler (Mini‐OHS) configuration was designed to prevent oversampling at low outflows but required drill bit of smaller diameter (0.8‐mm). Laboratory and numerical experiments demonstrated that both configurations obtained accurate flow‐weighted runoff samples when incorporated into the UBeTube. Flow rates in the Mini‐OHS were better correlated with runoff rates under constant‐flow ( R 2 = .992 vs. .965 for the Standard‐OHS) and variable‐flow conditions ( R 2 = .996 vs. .954 for the Standard‐OHS). Further modification of the Holey Sampler could also allow flow‐weighted sampling of other runoff quantification devices like flumes and weirs. Core Ideas: Surface runoff samples are needed to quantify pollutant transport processes. We developed an inexpensive, passive flow‐weighted sampling system for runoff. We tested versions with standard‐ and miniature‐sized sampling holes. Both configurations collected flow‐weighted samples during constant and variable flow. Sampler may be adapted to other runoff quantification systems.